1999
DOI: 10.1074/jbc.274.27.19195
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mammalian Legumain by Some Cystatins Is Due to a Novel Second Reactive Site

Abstract: We have investigated the inhibition of the recently identified family C13 cysteine peptidase, pig legumain, by human cystatin C. The cystatin was seen to inhibit enzyme activity by stoichiometric 1:1 binding in competition with substrate. The K i value for the interaction was 0.20 nM, i.e. cystatin C had an affinity for legumain similar to that for the papain-like family C1 cysteine peptidase, cathepsin B. However, cystatin C variants with alterations in the N-terminal region and the "second hairpin loop" that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
223
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(234 citation statements)
references
References 52 publications
9
223
1
1
Order By: Relevance
“…Previous studies showed that some typical cysteine proteinase inhibitors, as, for example, cystatins and E64 (44,45), cannot block the proteolytic activity of IdeS (6). Comparison of the crystal structures of IdeS and other proteinases reveals that overall differences between the active-site cleft of IdeS and other papain-like cysteine proteinases are responsible for the inability to affect IdeS activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that some typical cysteine proteinase inhibitors, as, for example, cystatins and E64 (44,45), cannot block the proteolytic activity of IdeS (6). Comparison of the crystal structures of IdeS and other proteinases reveals that overall differences between the active-site cleft of IdeS and other papain-like cysteine proteinases are responsible for the inability to affect IdeS activity.…”
Section: Discussionmentioning
confidence: 99%
“…Inspection of the aligned sequences of these isoforms in their surface regions focused attention on the ␤5-␤6 loop, positioned in the lower crown region (residues 71-76 containing the sequence Ile-AspAsn-Ser-Ile). This part of the sequence is similar to the consensus sequence (S/T)N(D/S)(M/I) found in three inhibitory cystatins C, E, and F ( Table 4) that bind to AEP in the nanomolar range (40). Interestingly, in macrocypin 4, the residue at position 72 is Lys, in contrast to the equipositioned Asn in macrocypins 1 and 3.…”
Section: Tablementioning
confidence: 80%
“…Thus, Asn-72 in macrocypins and Asn-69 in clitocypins are confirmed to be the residues responsible for the inhibition of AEP. Mycocypins are, in this respect, similar to cystatin C, which has two different binding sites, one for papain-like proteases and another for AEP (40).…”
Section: Table 3 Inhibition Constants Of Cathepsin V By Macrocypin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Na literatura. temos que legumaína é uma endopeptidase caracterizada por não ser afetada por esse clássico inibidor, porém por outras cistatinas (Alavarez-Fernandez et al, 1999). A isoforma da Fração Solúvel caracterizada nesse trabalho possivelmente pertence a essa família de enzimas, porém testes com outras cistatinas deverão ser realizados para se confirmar que as cisteíno proteases da Fração Solúvel são cisteíno proteases legumaína-like.…”
Section: Methodsunclassified